VDJdb: a curated database of T-cell receptor sequences with known antigen specificity. Issue Volume 46:Issue D1(2018) (1st September 2017) - Shugay, Mikhail; Bagaev, Dmitriy V; Zvyagin, Ivan V; Vroomans, Renske M; Crawford, Jeremy Chase; Dolton, Garry; Komech, Ekaterina A; Sycheva, Anastasiya L; Koneva, Anna E; Egorov, Evgeniy S; Eliseev, Alexey V; Van Dyk, Ewald; et al.
Abstract: The ability to decode antigen specificities encapsulated in the sequences of rearranged T-cell receptor (TCR) genes is critical for our understanding of the adaptive immune system and promises significant advances in the field of translational medicine. Recent developments in high-throughput sequencing methods (immune repertoire sequencing technology, or RepSeq) and single-cell RNA sequencing technology have allowed us to obtain huge numbers of TCR sequences from donor samples and link them to T-cell phenotypes. However, our ability to annotate these TCR sequences still lags behind, owing to the enormous diversity of the TCR repertoire and the scarcity of available data on T-cell specificities. In this paper, we present VDJdb, a database that stores and aggregates the results of published T-cell specificity assays and provides a universal platform that couples antigen specificities with TCR sequences. We demonstrate that VDJdb is a versatile instrument for the annotation of TCR repertoire data, enabling a concatenated view of antigen-specific TCR sequence motifs. VDJdb can be accessed at https://vdjdb.cdr3.net and https://github.com/antigenomics/vdjdb-db .